Balanced scorecard : translating strategy into action - Kaplan, Robert S. (HARVARD BUSINESS SCHOOL P. BostonUS, 1996)
Presents the balanced scorecard (BSC) as a strategic management system that translates mission and strategy into objectives and measures. Shows how to use measures, in each of four categories namely: financial, customer, internal business process, and learning and growth. Uses Part 1 to describe the construction of the BSC. Covers the fundamentals of building objectives and measures in each of the four categories. Uses Part 2 to explain how companies are using the BSC to enhance alignment and accountability; to establish long term targets for strategic measures; and, to facilitate strategic learning.